CONVERGENCE OF AN IMPLICIT ITERATION PROCESS FOR A FINITE FAMILY OF GENERALIZED I-ASYMPTOTICALLY NONEXPANSIVE MAPPINGS - Temir, S. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2012)
In this paper, we consider strong convergence of implicit iteration process to common fixed point for generalized I-asymptotically nonexpansive mappings. The main results extend to finite family of generalized I-asymptotically nonexpansive mappings in a Banach space.